Hypocretin/orexin influences chronic sleep disruption injury in the hippocampus - Nick, Henry; Fenik, Polina; Zhu, Yan; Veasey, Sigrid (Frontiers in Aging Neuroscience, 2022)
Chronic sleep disruption is a risk factor for Alzheimer’s disease (AD), yet mechanisms by which sleep disturbances might promote or exacerbate AD are not understood. Short-term sleep loss acutely increases hippocampal amyloid β (Aβ) in wild type (WT) mice and long-term sleep loss increases amyloid plaque in AD transgenic mouse models. Both effects can be influenced by the wake-promoting neuropeptide, hypocretin (HCRT), but whether HCRT influences amyloid accumulation independent of sleep and wake timing modulation remains unclear. Here, we induced chronic fragmentation of sleep (CFS) in WT and HCRT-deficient mice to elicit similar arousal indices, sleep bout lengths and sleep bout numbers in both genotypes. We then examined the roles of HCRT in CFS-induced hippocampal Aβ accumulation and injury. CFS in WT mice resulted in increased Aβ42 in the hippocampus along with loss of cholinergic projections and loss of locus coeruleus neurons. Mice with HCRT deficiency conferred resistance to CFS Aβ42 accumulation and loss of cholinergic projections in the hippocampus yet evidenced similar CFS-induced loss of locus coeruleus neurons. Collectively, the findings demonstrate specific roles for orexin in sleep disruption hippocampal injury. Significance statement Chronic fragmentation of sleep (CFS) occurs in common conditions, including sleep apnea syndromes and chronic pain disorders, yet CFS can induce neural injury. Our results demonstrate that under conditions of sleep fragmentation, hypocretin/orexin is essential for the accumulation of amyloid-β and loss of cholinergic projections in the hippocampus observed in response to CFS yet does not influence locus coeruleus neuron response to CFS.